Pheretimoid earthworms (Clitellata: Megascolecidae) cultivated in a vermifacility in Los Baños, Laguna, Philippines, with description of a new species - Aspe, Nonillon M.; Obusan, Marie Christine M. (Zootaxa, 2023)
We report two pheretimoid earthworm species cultivated in Folia Tropica vermifacility in Los Baños, Laguna, Philippines. One species is Pheretima losbanosensis sp. nov., which belongs to P. dubia group in Sims & Easton 1972, characterized by having three pairs of spermathecal pores in 6/7–8/9. It has an adult size of 220–228 mm x 8–9 mm; and has 26–36 and 56–66 setae on vii and xx, respectively. The other species is Metaphire bahli Gates, 1945, characterized by having three pairs of spermathecal pores in 6/7–8/9 and post-clitellar genital markings at 17/18 and 18/19. The vermicasts of the two species are commercially produced and are harvested as organic fertilizers. We promote the utilization of native species for vermiculture and vermicomposting rather than using the introduced vermicomposting species African nightcrawler Eudrilus eugeniae.